(untitled) (Research, Society and Development, 2020)
This article presents the report of an activity developed in the Academic Master in Humanities and Languages, the objective is to report a practice of producing educational content capable of conducting reflection and study with teachers, and its fundamental theme is interdisciplinarity. The qualitative and descriptive activity comprises the report of the experience of making a video - here metaphorically called as an interdisciplinary pill of knowledge. The interdisciplinary theme is presented with emphasis on characteristics of the phenomenon in its historical and epistemological aspects that may offer methodological options in order to stimulate the teacher to adhere to interdisciplinary practices in the daily classroom.